Prescription of Benzodiazepines and Related Drugs in Patients with Mild Cognitive Deficits and Alzheimer’s Disease - Hessmann, Philipp; Dodel, Richard; Baum, Erika; Müller, Matthias J.; Paschke, Greta; Kis, Bernhard; Zeidler, Jan; Klora, Mike; Reese, Jens-Peter; Balzer-Geldsetzer, Monika (Pharmacopsychiatry, 2019)
Introduction Benzodiazepines and related drugs (BZDR) should be avoided in patients with cognitive impairment. We evaluated the relationship between a BZDR treatment and the health status of patients with Alzheimer’s disease (AD).Methods Cross-sectional study in 395 AD patients using bivariate and multiple logistic analyses to assess correlations between the prescription of BZDR and patients’ characteristics (cognitive and functional capacity, health-related quality of life (HrQoL), neuropsychiatric symptoms).Results BZDR were used in 12.4% (n=49) of all participants. In bivariate analyses, the prescription was associated with a lower HrQoL, a higher need of care, and the presence of anxiety. Multivariate models revealed a higher risk of BZDR treatment in patients with depression (OR 3.85, 95% CI: 1.45 – 10.27). Community-dwelling participants and those treated by neurologists/psychiatrists had a lower risk of receiving BZDR (OR 0.33, 95% CI: 0.12 – 0.89 and OR 0.16, 95% CI: 0.07 – 0.36).Discussion The inappropriate use of BZDR conflicts with national and international guidelines. We suggest evaluating indications and treatment duration and improving the knowledge of alternative therapies in healthcare institutions.
Keywords: benzodiazepines; dementia; depression; neuropsychiatric specialists